Curriculum for a New Four-Year Bachelor's Degree in Intelligent Systems Engineering - Solo, Ashu M. G. (2023 Congress in Computer Science, Computer Engineering, & Applied Computing (CSCE), 2023)
This research paper proposes a curriculum for a four-year bachelor's degree in intelligent systems engineering with courses in knowledge-based systems, fuzzy logic, neural networks, evolutionary computation, machine learning, image processing, computer vision, pattern recognition, data science, control systems, intelligent control systems, robotics, digital signal processing, software development, calculus, algebra, other mathematics, physics, biology, etc. This degree will allow graduates to have a good understanding of all of the main branches of intelligent systems engineering as well as relevant subjects in electrical and computer engineering.